Las estrategias metodológicas y su importancia en el adecuado manejo del aula en la educación inicial de niños/as de 1 a 3 años del centro infantil Step By Step en la provincia de Cotopaxi, cantón Latacunga parroquia Juan Montalvo en el año lectivo 2014-2015 - Molina Molina, Sandra Paulina (2016)
The work of the nursery school seeks the develop of effective skills in children generating learning opportunities through the pedagogical, interactive and motivational process. This research work is set out to determine the methodological strategies with the classroom handle in initial education to children from 1 to 3 years old under the weak implementation of strategies which were denoted in the initial children at Step by Step educative center, the research work revealed a space of passive and traditional teaching. The relation to the applied method in the investigative process was developed the induction and deduction in the relation to the scientific study, the technique was direct observation in the learning classroom with the initial children, in addition the survey and the interview were applied in order to contrast the field research. As principal results to determine that it is necessary the recreational workshops for children, which are planted as a the main purpose. Finally, it concludes that the application of methodological strategies according to children ages, they encourage the teaching learning process in the classroom.